2006
DOI: 10.1111/j.1365-2958.2006.05398.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete alanine scanning of the two‐component lantibiotic lacticin 3147: generating a blueprint for rational drug design

Abstract: SummaryLantibiotics are post-translationally modified antimicrobial peptides which are active at nanomolar concentrations. Some lantibiotics have been shown to function by targeting lipid II, the essential precursor of cell wall biosynthesis. Given that lantibiotics are ribosomally synthesized and amenable to sitedirected mutagenesis, they have the potential to serve as biological templates for the production of novel peptides with improved functionalities. However, if a rational approach to novel lantibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
166
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(174 citation statements)
references
References 50 publications
8
166
0
Order By: Relevance
“…Of the other peptides produced, none were more active than the natural peptides, and overall, it was found that the A2 peptide (particularly it's N terminus) was more tolerant to change than A1. 40 A further mutagenesis study was undertaken to probe for mutants that decreased the activity of the natural peptides. More mutants were detected for A1 (as it is less flexible to amino-acid alteration) than A2.…”
Section: Lacticin 3147mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the other peptides produced, none were more active than the natural peptides, and overall, it was found that the A2 peptide (particularly it's N terminus) was more tolerant to change than A1. 40 A further mutagenesis study was undertaken to probe for mutants that decreased the activity of the natural peptides. More mutants were detected for A1 (as it is less flexible to amino-acid alteration) than A2.…”
Section: Lacticin 3147mentioning
confidence: 99%
“…On one hand, Ross, and coworkers have utilized a mutagenesis approach to produce a large number of single amino-acid mutants to examine the importance of each amino acid in the two-component peptide system. [39][40][41][42] On the other hand, Vederas and coworkers have used chemical synthesis to investigate the importance of the lan and melan rings with a view towards producing simpler and more stable analogs. [43][44][45] HALODURACIN Haloduracin is a two-component lantibiotic isolated from Bacillus halodurans consisting of a globular a-peptide resembling the class B lantibiotics and an elongated b-peptide similar to class A.…”
Section: Lacticin 3147mentioning
confidence: 99%
“…These peptides do however share one common charge-related feature in that all possess a conserved glutamate residue (referred to in the context of nukacin ISK-1 above) which is thought to play a key role in receptor binding, and mutagenesis of which resulted in the abolition of antimicrobial activity. 10,33,40,41 In contrast, β peptides are linear, appear to represent the pore-forming component and thus more closely resemble classical cationic antimicrobial peptides. Bliβ of licheniciden is the only β component which contains negatively charged residues and as a result has a neutral rather than a cationic charge.…”
Section: Investigating the Importance Of Charged Residues In Lantibiomentioning
confidence: 99%
“…The nisin peptides referred to are derivatives of two natural forms of nisin, i.e., nisin A and Z, which differ by one amino acid in that nisin A and Z have a histidine and globular do not resemble classical cationic antimicrobial peptides. Indeed two of these peptides, Ltnα of Lacticin 3147, 33,37 and putative Pnmα of Pneumococcin SP23-BS72, 14 have a net neutral charge. These peptides also resemble a number of one peptide lantibiotics such as the aforementioned mersacidin and actagardine which are anionic, 7,10,17,38,39 thereby establishing that an overall net positive charge is not an essential pre-requisite for this extended group of peptides.…”
Section: Investigating the Importance Of Charged Residues In Lantibiomentioning
confidence: 99%
“…However, LanM enzymes reveal low substrate specificity under laboratory conditions, a property that has been exploited for the generation of variants of the natural products (12)(13)(14). Wondering whether organisms in nature have taken advantage of this substrate promiscuity to generate natural product libraries with a single streamlined biosynthetic toolset, we conducted a search of the sequenced bacterial genomes for cases where a single bacterium can produce multiple lanthionine-containing peptides using the same LanM enzyme.…”
mentioning
confidence: 99%